Geographies of food beyond food: transfiguring nexus-thinking through encounters with young people in Brazil. (13th June 2022) - Zara, Cristiana; Coles, Benjamin; Hadfield-Hill, Sophie; Horton, John; Kraftl, Peter
ABSTRACT: Engaging contemporary forms of nexus-thinking with interdisciplinary food scholarship and childhood and youth studies, this paper explores the social, cultural and political implications of young people's entangled connections with – and beyond – food. The paper draws on a large-scale research project investigating young Brazilians' relationships with and understandings of the water-energy-food nexus. Based upon ethnographic, mixed-methods research, we attend to young people's everyday, material experiences of water-energy-food, and call for a transfigured nexus-thinking, alive with the lives, cares, relationalities and politics at the heart of 'the nexus'. Through examples ranging from participants' routines, rhythms and mobilities to experiences of food insecurity, we show how young people express a range of social-political sensibilities that articulate with food and expand nexus-thinking in several interconnected ways. First, by exposing the multi-scalar and multi-temporal processes underlying their everyday 'nexuses'. Second, by destabilizing the water-energy-food nexus to include ever-new elements emerging from lived experiences of resource access. Third, by showing the embeddedness of resources in the cultures, politics and social fabric of communities. Fourth by uncovering the workings of social difference in articulating nexus dis/connections. It is through these encounters with youths in Brazil that we propose a (re)politicisation and critical transfiguration of nexus thinking.